Genome-wide Identification, Classification, Expression and Duplication Analysis of GRAS Family Genes in Juglans regia L. - Shaowen Quan (Nature Portfolio, 2019)
Abstract Fifty-two GRAS genes are identified in walnut genome. Based on the evolutionary relationship and motif analysis, the walnut GRAS gene family was divided into eight subfamilies, and the sequence features analysis of JrGRAS proteins showed that the JrGRAS protein sequences were both conserved and altered during the evolutionary process. Gene duplication analysis indicated that seven GRAS genes in walnut have orthologous genes in other species, and five of them occurred duplicated events in walnut genome. Expression pattern analysis of the GRAS family genes in walnut showed that two JrGRAS genes (JrCIGRa-b and JrSCL28a) were differentially expressed between flower bud and leaf bud (p < 0.01), and two JrGRAS genes (JrCIGRa-b and JrSCL13b-d) were differentially expressed between the different development stages of flower buds transition (p < 0.01), besides, three hub genes (JrGAIa, JrSCL3f and JrSHRc) were identified by co-expression analysis, which suggested these GRAS genes may play an important role in regulating the development of apical meristem in walnut. This study laid a foundation for further understanding of the function of GRAS family genes in walnut.